Cakupan Penggunaan, Kepuasan dan Kepercayaan Masyarakat Jabodetabek terhadap Aplikasi Mobile JKN - dati, Catur Rosi; Annisa Zahra Aulia; Balqis Ramadhina Kosya; Gianluigi Fahrezi; Muhammad Willman Al-Farizy; Mu’minatus Solihah; Tsaniya Nurul Fasya (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
The Social Security Administrator for Health (BPJS Kesehatan) as the organizer of Indonesia’s national health insurance continues to innovate through digital technology to enhance service quality and expand membership coverage. One such innovation is the Mobile JKN application, designed to facilitate participant registration, data management, and access to health services at both primary and referral healthcare facilities. However, the utilization of Mobile JKN in the Greater Jakarta area (Jabodetabek) remains relatively low, with only 1,027,233 users recorded as of January 2, 2019. This study aimed to describe the extent of Mobile JKN utilization, public trust, and user satisfaction toward the application. A cross-sectional design was employed involving 644 respondents selected through quota sampling, with data analyzed using univariate methods. Results showed that among 644 respondents, 241 individuals (54.8%) reported using the Mobile JKN application. The most frequently used features were registration for healthcare facilities (24.9%), BPJS membership registration (21.7%), and access to information on nearby healthcare facilities (22.3%). Most users demonstrated high trust in the credibility and data security of the application and expressed satisfaction with various dimensions of information and system quality, including content, accuracy, format, ease of use, and timeliness. Increasing Mobile JKN utilization requires intensive public outreach through social media and influencer engagement, developing a WhatsApp information channel, and adding promotive and preventive health information features. Keywords: Mobile JKN, user trust, service satisfaction